The Use of Silver in Cesarean Wound Bandages: A New Way to Decrease Infection and Healthcare Costs [36P]. (May 2020) - Grossman, Tracy; Fields, Jessica; Chan-Akeley, Rosalyn; Dayal, Ashlesha
Abstract : INTRODUCTION: Post-cesarean surgical site infection (SSI) occurs after 3.7–9.8% of cesarean deliveries and is associated with significant morbidity and healthcare costs. Silver has antimicrobial properties and bandages impregnated with it are associated with decreased rates of SSI in non-obstetric surgery. Our objective was to compare the rates of deep and superficial cesarean SSI before and after the institution of silver-impregnated bandages and to analyze related healthcare costs. METHODS: This was a retrospective cohort study comparing the rates of cesarean-related SSI five months before and after the institution of silver-impregnated bandages and associated healthcare costs. Data was analyzed using chi-square and Fisher's exact test. RESULTS: There were 1, 044 cesarean deliveries and 33 wound-related emergency department (ED) presentations during the study period. The demographics of the standard-of-care (n=538) and silver-bandage (n=506) groups were similar. The overall rates of deep and superficial SSI were 0.8% (n=8) and 0.6% (n=6) respectively. The use of silver-bandages was associated with a decrease in the rate of deep SSI (0.6% (n=3) vs 0.9% (n=5), P= .2) and superficial SSI (0.4% (n=2) vs 0.7% (n=4), P= .3). There were 24% fewer ED presentations in the silver-bandage group (13 vs 17) and one wound dehiscence requiring re-operation and negative-pressure wound-therapy, which was in the standard-of-care group. Healthcare costs related to SSI, ED presentations and long-term wound care were 29% less in the silver-bandage group. CONCLUSION: The use of silver-impregnated bandages was associated with a decreased rate of cesarean SSI and decreased healthcare costs. Longer-term studies will likely yield statistically significant decreases in SSI and healthcare costs, as post-cesarean SSI is a rare outcome.